ANALYSIS OF PRODUCTION PROCESS OF SULFURIC ACID APPLYING THE FUNDAMENTAL PRINCIPLES To DESIGN OF SUSTAINABLE INDUSTRIAL PROCESSES - Loayza P., J. (2013)
The principles to design a sustainable industrial process can be applied to the design of a new process or to evaluate an existing process and make it sustainable. Need to be considered for the design and evaluation raised by the Green Chemistry, Green Engineering, Cleaner Production and Industrial Ecology. This document is referenced production of sulfuric acid, a product used as raw material or input for the manufacture of a wide variety of products, such as fertilizers, dyes, catalysts, etc. The raw materials used for manufacturing are analyzed, highlighting the processes from petrochemical sulfur and roasting gases.